Digital storytelling: Menstimulasi minat spiritualitas pada anak Generasi Alfa di era posdigital - Sidabutar, Dewi Lidya; Prasetya, Didimus Sutanto B. (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2024)
The issue of the spirituality of Generation Alpha children must start by mapping their digital-based interests. One way to increase interest in the process of learning Christian education is through a storytelling approach. This article offers digital-based storytelling to build and develop the spiritual interests of Generation Alpha children. This article uses a literature study through descriptive searches on various research references on storytelling and Generation Alpha in the post-digital era. Research shows the power of storytelling in improving the abilities of Generation Alpha children. We conclude that the spirituality of Generation Alpha begins with the interest in spirituality itself, which can be stimulated through digital storytelling. Abstrak Persoalan spiritualitas anak generasi Alfa harus dimulai dari memetakan minat mereka yang berbasis digital. Salah satu cara untuk meningkatkan minat dalam proses belajar pendidikan kristiani adalah dengan pendekatan storytelling. Artikel ini bertujuan untuk menawarkan penggunaan storytelling bebasis digital guna membangun hingga mengembangkan minat spiritualitas anak generasi Alfa. Artikel ini menggunakan studi pustaka, melalui penelusuran secara deskriptif pada berbagai referensi hasil riset tentang storytelling dan generasi Alfa di era posdigital. Penelusuran riset memperlihatkan kekuatan storytelling dalam meningkatkan kemampuan anak generasi Alfa. Kami menyimpulkan bahwa spiritualitas generasi Alfa dimulai dari minat spiritualitas itu sendiri, yang dapat distimulasi melalaui digital storytelling.